Early detection of breast cancer using wave elliptic equation with high performance computing - Alias, Norma; Rosly, Nur Syazana; Satam, Noriza; A. Ghaffar, Zarith Safiza; Islam, Md. Rajibul (2008)
Breast cancer is the commonest female malignancy in Malaysia and all over the world. The incidence of breast cancer in Malaysia is estimated to be around 27 per 100,000 populations, with close to 3,000 new cases annually. The numerical solution is applied to solve a mathematical model in medicine field. The wave equation can be used as mathematical models in science and engineering fields especially for biological aspects of electromagnetic wave. This paper focuses on the implementation of parallel algorithm for the simulation of breast cancer tumor using two dimensional Helmholtz’s wave equation on a distributed parallel computer system (DPCS). The numerical finite-difference method is chosen as a platform for discretizing the wave equations. The mathematical model of Helmholtz’s model is used to visualize the growth of breast cancer. Parallel Virtual Machine (PVM) is emphasized as communication platform in parallel computer system. The performance of the parallel computing will be analyzed in terms of time execution, speed up, efficiency, effectiveness and temporal performance